(untitled) (CIPEEX, 2025)
This article analyzes the exclusive application of Brazil’s SELIC rate (Special System for Settlement and Custody) to the monetary update of tax refunds (indébito tributário) since January 1, 1996, emphasizing the prohibition against combining it with any other interest or indexation metrics. It is a doctrinal, bibliographic, and case-law-based study that identifies the legal foundations and scope of SELIC under the National Tax Code and the guidance of the superior courts. The method is analytical, merging literature review with the examination of precedents from the Superior Court of Justice and the Federal Supreme Court to assess whether SELIC operates as a single index covering both monetary correction and default interest, and whether any combination would amount to double counting. The findings show a prevailing understanding in the Superior Court of Justice that SELIC suffices to restore the value of undue tax payments and bars accumulation with remuneratory interest or other correction indices, thereby promoting decisional uniformity, predictability, and legal certainty in tax refunds and set-offs. The conclusion is that SELIC’s exclusive use prevents overvaluation of taxpayers’ credits and reduces disputes over quantification; at the same time, a systematic, Constitution-consistent reading is advisable to address exceptional circumstances in light of principles such as legality, equality, and the prohibition of confiscation.